CALCULATION OF PKA OF PHENOLS AND THIOLS AS A MODEL TO EVALUATE THE ACIDITY OF CATALYSTS ON ACTIVATED CHARCOAL: UDC 541.128 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
It was calculated a pKa values for set of the phenols and thiols. The pKa values don't deviate from its experimental values more than one unit. Tested method can be applied to theoretical predication of the acidity of activated charcoal catalyst with different functional groups on its surface.
Keywords: activated charcoal, acidity, catalysis